2010
DOI: 10.1603/en10131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Japanese Barberry (Ranunculales: Berberidaceae) Removal and Resulting Microclimatic Changes on Ixodes scapularis (Acari: Ixodidae) Abundances in Connecticut, USA

Abstract: Japanese barberry (Berberis thunbergii de Candolle) is a thorny, perennial, exotic, invasive shrub that is well established throughout much of the eastern United States. It can form dense thickets that limit native herbaceous and woody regeneration, alter soil structure and function, and harbor increased blacklegged tick (Ixodes scapularis Say) populations. This study examined a potential causal mechanism for the link between Japanese barberry and blacklegged ticks to determine if eliminating Japanese barberry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 31 publications
1
50
0
2
Order By: Relevance
“…The study results suggest that A. mellifera and A. drepanolobium encroachment provides a conducive environment for the survival of ticks which is in line with Bertrand and Wilson (1996) who reported that ticks in open fields suffered higher mortality rates than those in canopied habitats. A previous study by Scott and Jeffrey (2010) found that adult tick density was positively correlated with percent coverage of live Japanese barberry. Adult-stage tick density was increased by 1,111.1 ha −1 after the control actions only in the control plot (T5) probably due to their ability to escape from the plots that were cleared off encroaching trees/shrubs species to the plots that were untouched, i.e.…”
Section: Bush Control Effects On Vegetation Structure and Basal And Lmentioning
confidence: 86%
“…The study results suggest that A. mellifera and A. drepanolobium encroachment provides a conducive environment for the survival of ticks which is in line with Bertrand and Wilson (1996) who reported that ticks in open fields suffered higher mortality rates than those in canopied habitats. A previous study by Scott and Jeffrey (2010) found that adult tick density was positively correlated with percent coverage of live Japanese barberry. Adult-stage tick density was increased by 1,111.1 ha −1 after the control actions only in the control plot (T5) probably due to their ability to escape from the plots that were cleared off encroaching trees/shrubs species to the plots that were untouched, i.e.…”
Section: Bush Control Effects On Vegetation Structure and Basal And Lmentioning
confidence: 86%
“…Silt fence barriers, made from polypropylene plastic fabric, were shown to reduce the abundance of I. scapularis adults, but not nymphs, in pastures (Carroll and Schmidtmann 1996). Two woodland studies in Connecticut showed that removal of the invasive Japanese barberry ( Berberis thunbergii de Candolle) shrub, which previously was found to be associated with elevated abundance of host-seeking I. scapularis in Maine (Lubelczyk et al 2004, Elias et al 2006), could substantially reduce the abundance of host-seeking I. scapularis adults as well as B. burgdorferi -infected adults (Williams et al 2009, Williams and Ward 2010). Other studies have demonstrated strong negative impacts of burning or mowing on the abundance of host-seeking I. scapularis adults (Rogers 1953, Wilson 1986, Gleim et al 2014).…”
Section: Suppression Of I Scapularis and B Burgdorferi With A Singlmentioning
confidence: 99%
“…These approaches include removal of specific plants associated with increased tick abundance like Japanese Barberry; use of herbage that is less attractive to deer such as ferns, native grasses, and unpalatable tree species such as spruce; and desiccant barriers (gravel or wood chips) at the boundary of high-(forest edge) and low-risk zones (lawns). 71,97 Finally, tick unfriendly zones can be created by integrating landscape structures (eg, a raised deck) and management practices (eg, grass cutting, scrub removal, xeriscaping). An excellent summary of vegetation management for tick control is provided in Ref.…”
Section: Vegetation or Landscape Managementmentioning
confidence: 99%